Gambaran bilirubin dan urobilinogen urin pada pasien tuberkulosis paru dewasa di RSUP Prof. Dr. R. D. Kandou Manado - Makay, Faleriano; Rambert, Glady I.; Wowor, Mayer F. (Universitas Sam Ratulangi, 2016)
Abstract: Tuberculosis is an infectious disease caused by the bacillus Mycobacterium tuberculosis. Antituberculosis drugs prescribed to TB patients is hepatotoxic drug. Liver damage caused by side effects of the drugs will cause an alteration in urinary bilirubin and urobilinogen level. This study was aimed to obtain the profile of urinary bilirubin and urobilinogen in adult pulmonary tuberculosis patients at Prof. Dr. R. D. Kandou Hospital Manado from October to November 2016. This was an observational descriptive study. Samples obtained by using random sampling urine from all pulmonary tuberculosis patient that met the inclusion criteria. The results showed that according to urinary bilirubin and urobilinogen examination in 30 patients, most of them were in normal level. Only 6 out of 30 patients has bilirubinuria in this urinary bilirubin examination. In urinary urobilinogen examination, all results is in normal level. Conclusion: Urinary bilirubin and urobilinogen examination in this research was normal in general, bilirubinemia was found only in some patients.Keywords: pulmonary tuberculosis, urinary bilirubin, urinary urobilinogenÂ Abstrak: Tuberkulosis (TB) merupakan penyakit menular yang disebabkan oleh basil Mycobacterium tuberculosis. Obat antituberkulosis yang diberikan pada pasien TB bersifat hepatotoksik. Kerusakan hepar yang disebabkan oleh efek samping obat tersebut akan menyebabkan perubahan pada kadar bilirubin dan urobilinogen urin. Tujuan penelitian untuk mengetahui gambaran bilirubin dan urobilinogen urin pada pasien tuberkulosis paru dewasa di RSUP Prof. Dr. R. D. Kandou Manado. Jenis penelitian ialah deskriptif observasional, untuk mendapatkan data tentang bilirubin dan urobilinogen urin pada pasien tuberkulosis paru dewasa di RSUP. Prof. Dr. R. D. Kandou Manado pada Oktober-November 2016. Sampel penelitian adalah sampel urin sewaktu dari semua pasien tuberkulosis paru yang memenuhi kriteria inklusi. Hasil penelitian memperlihatkan berdasarkan pemeriksaan bilirubin dan urobilinogen urin pada 30 pasien, sebagian besar kadarnya normal. Hanya 6 dari 30 pasien yang mengalami bilirubinuria pada pemeriksaan bilirubin urin. Pada pemeriksaan urobilinogen urin semua hasil dalam batas normal. Simpulan: Pemeriksaan bilirubin dan urobilinogen urin pada umumnya normal, hanya beberapa pasien yang mengalami bilirubinuria.Kata kunci: tuberkulosis paru, bilirubin urin, urobilinogen urin